Hubungan Kepuasan Pelayanan Petugas Kesehatan Dengan Minat Kunjungan Ulang Pasien Di Puskesmas Bukit Hindu - Wijaya, Budi; Carolina, Putria; Rosela, Kristin (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Patient satisfaction with healthcare services is an important indicator in assessing service quality, especially in primary healthcare facilities such as Puskesmas. The phenomenon at Puskesmas Bukit Hindu shows fluctuations in the number of patient visits over the past three years, with a decline in 2023 despite an increase in 2024. This indicates that patient satisfaction with healthcare services may influence the interest in return visits. Objective to determine the relationship between healthcare service satisfaction and the interest in return visits among patients at Puskesmas Bukit Hindu. This study used a correlational design with a cross-sectional approach. The sampling technique used accidental sampling with a total of 40 participants. Data collection using a questionnaire was conducted from June 16 to 30, 2025 and statistical analysis was performed using the Chi-Square test. From 40 respondents, it was found that patient satisfaction with healthcare services who were dissatisfied and not interested in return visits consisted of 12 respondents (85.7%), while those interested in return visits were 2 respondents (14.3%). Furthermore, among those satisfied with healthcare services, 3 respondents (11.5%) were not interested in return visits, and 23 respondents (88.5%) were interested in return visits. The Chi-Square test yielded a p-value of 0.000, which is less than the significance level of p < 0.05, thus H1 is accepted, indicating a relationship between healthcare service satisfaction and the interest in return visits among patients at UPTD Puskesmas Bukit Hindu. There is a relationship between healthcare service satisfaction and the interest in return visits among patients. It is hoped that Puskesmas Bukit Hindu Palangka Raya can improve the resources of healthcare personnel, facilities, and infrastructure to support healthcare services